Catholic sensationalism and Victorian literature - Moran, Maureen (Liverpool English texts and studies ;, 2007)
Catholic Sensationalism and Victorian Literature offers a highly original examination of Victorian cultural and social conventions through readings of popular literary representations of Roman Catholicism. Maureen Moran argues that Catholic sensationalism provided a rich imaginative resource for Victorians of all denominations (and none) through which a range of cultural contradictions and conflicts could be explored and alternative identities proposed. Previous studies of Catholicism in the period have focused on notions of the exotic, corrupt religious Other which is inscribed as the implaca.